Social Norms or Enforcement? A Natural Field Experiment to Improve Traffic and Parking Fine Compliance - Mathias Sinning; Yinjunjie Zhang (Institute of Labor Economics (IZA), 2021)
Very little is known about the efficient collection of fines despite their indispensable contribution to local government budgets. This paper fills an important gap in the literature by studying the effectiveness of deterrence (enforcement) and non-deterrence (social norms) letters that aim to improve the collection of traffic and parking fines. We discuss potential mechanisms through which these letters may affect fine compliance and present results from a natural field experiment that was implemented in collaboration with the government of the Australian Capital Territory (ACT). We find that both letters increase fine payments significantly relative to a control group that did not receive a letter. The effect of the enforcement letter is stronger than that of the social norms letter. Our analysis of heterogenous treatment effects indicates that addressing social norms does not change the behavior of young offenders, those who committed a speeding offence, those with a long outstanding debt and those with a debt above the median. In contrast, the enforcement letter is generally effective across subgroups.
Keywords: H26; K42; C93; 330; fine compliance; natural field experiment; nudges; enforcement; social norms